A framework of strategic building adaptation action for managing multi-storey low-cost public housing: in Kuala Lumpur, Malaysia / Siti Aida Samikon - Samikon, Siti Aida (2018)
Public housing is one of the importantly affordable homes for all citizens, particularly in the low-income group. The government has implemented various public housing schemes. Pro-active assessment of the low-cost public housing performance is essential to monitor building condition and guide future public housing management. This research aims to identify the practice and procedure and to propose a framework for building adaptation and eventually improve the management of existing multi-storey low-cost public housing in Malaysia. The objectives of this research is to determine the nature and pattern of building adaptation and its relationships between building attribute or characteristics; to identify current condition of low-cost public housing and its potentiality of building adaptation factors in managing multi-story low-cost public housing in Malaysia; and to develop a framework for building adaptation strategy for managing multi-storey low-cost public housing in Malaysia. In this research, data collections are collected from the selected public housing, limited to multi-storey housing, rented, and constructed for more than 10 years. Selected 6 housing areas of rented public housing is acquired from Public Housing Program (PPR) DBKL. This questionnaire survey conducted to obtain the experts' view on the constructive determinants of adaptation factors and potential action for managing existing public housing. 36 respondents participated in this survey. From the result of the survey, semi-structured interviews conducted to selected experts and 11 respondents agreed to participate in semi-structure interview to provide further validity. An observation and inspection of building condition and residents satisfaction was conducted to 6 selected Public Housing Program (PPR). A sample size of residents' satisfaction was 501 respondents. The research findings provide relevant data and issues to enhance physical management requirement and serious consideration to sustainable adaptation, which the entire problems concurrently in public housing facilities can be well treated. The framework in this research is an outline and connection of planning, assessment process, procedures and also building adaptation strategies in managing multi-storey low-cost public housing. The framework's aim is to provide a guideline as a guidance and reference for stakeholders involves in managing building adaptation for multi-storey low-cost public housing.